Perancangan Sistem Informasi Akademik Berbasis Web (Studi Kasus SMK Insan Madani) - Eva Rahmawati; . Rachmat (Universitas Bina Sarana Informatika, 2018)
Academic Information System at SMK Insan Madani still done manually. In the processing of academic data is still a lot kekuranngan that occurs, because the existing system still uses sheets of paper and archives so that it can cause data that is easily lost or damaged. Development of Web-Based Academic Information System In SMK Insan Madani aims to support and facilitate the existing academic system in SMAN Insan Madani so it is expected to be perceived by the students and teachers and other staff existing in the school. In the development of academic system the authors use data collection techniques that is observation, interview and literature study. Programming language used in designing and implementing the architectural information system of PHP is PHP and data base used is MySql. The things contained in this system include various academic information such as school information teacher data, student data and news about school information that is expected to help the school reduce errors in the process of recording data and reduce errors in the making of reportsin the process of recording data and reduce errors in the making of reports